Re-visualising innovative online learning spaces in an early childhood teacher education programme - Lesley Pohio; Maryann Lee (Flexible Learning Association of New Zealand, 2012)
This paper presents a critical examination of the challenges and rewards of re-visualising and designing an innovative online space for a first-year Bachelor of Education (BEd) Early Childhood Education (ECE) course, Visual Arts in the Early Years. The perspectives presented are drawn from a collaborative project between the course lecturer and learning designer. Central to the creation of this online learning space were the underpinning values and philosophy of the early childhood curriculum Te Whāriki (Ministry of Education [MoE], 1996). With this as our guide, we set out to create a rich visual online learning experience that reflected the creative learning environments in early childhood education. The challenge was how to transform a dynamic and fluid face-to-face teaching and learning context into an online mode. This engendered considerable rethinking not only of the content, but the conceptual framework that informs best practice in e-learning. That is, the educational experience supported a conceptual framework that promoted social, cognitive and teaching presence (Garrison & Anderson, 2003). Key considerations for designing this learning experience were to incorporate strong visual provocations, multiple pathways to learning, opportunities for collaboration and reflection, as well as a holistic and integrated approach. In order to capture the unique nature of the course in the proposed design, it was essential to understand the underlying principles and values that informed the course. As Edwards, Gandini, and Forman (1998, p. 177) assert; "the space has to be a sort of aquarium that mirrors the ideas, values, attitudes, and cultures of the people who live within it." It is argued that, without these beliefs being inherent in the design, the online learning environment that supports the depth of engagement and critical reflection by the learner is compromised.